Mapping of Road Pavement Conditions on the Cikampak Cicadas to the Segog Pamijahan Road Section - Rantelino, Owen; Suharnoto, Yuli; Sudibyo, Tri; Sutoyo (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Roads are one of the land transportation infrastructures that have a vital role in supporting community activities. Road damage is often encountered in various places. If left unchecked, handling road damage will cost a lot. The purpose of this study is to identify the type and extent of damage from road pavement and drainage in the study area, as well as determine handling recommendations for road pavement using the Bina Marga method. The method used is the Bina Marga method and the main output of this method is the value of the Priority Order (UP) and the recommendation for handling the observed road. The results of the study showed that the most common type of damage encountered at the study site was elongated cracks with a total area of 582.44m2, and lateral cracks were damages with the smallest total area, which was 6.27 m2. The value of road condition obtained from summing the number of damage in each segment showed that the condition value of 7 was mostly owned by the road segments at the research site, namely 18 segments, while the condition values 3 and 6 were only owned by 1 segment. Recommendations for handling the east side drainage were obtained as a result that 27 segments require routine maintenance, 18 segments require periodic maintenance and 10 segments require addition to the drainage system. The drainage on the west side was obtained as a result of 35 road segments requiring routine maintenance, 14 road segments requiring periodic maintenance and 6 road segments requiring addition to the drainage system. The recommendations for handling on the road were obtained as a result that 10 road segments require routine maintenance, 26 road segments require periodic maintenance and 19 road segments require improvement with the required handling costs of Rp 39,857,105, Rp 302,529,219 and Rp 1,719,020,425 respectively.